Athenry Dominican Priory, south nave wall, niche, arch and hood - O'Donovan, Danielle (My University, 2008)
Arch and hood moulding of eastern niche in south nave wall. Moulding of arch from inner to outer face comprises: hollow, roll-and-fillet, flat surface, roll-and-fillet, right-angled rebate, flat surface of wall. From outer to inner face, hood comprises: frontal fillet, hollow, hollow, quarter roll, hollow.
Niche
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Dominican; Late Medieval; roll-and-fillet moldings; roll moldings; moldings, hollow; hood moldings